2002
DOI: 10.1002/ana.10146
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐mediated suppression of Vβ5.2/5.3+ T cells in multiple sclerosis: Results from an MRI‐monitored phase II clinical trial

Abstract: The objective of this study was to evaluate the safety and efficacy of the humanized antibody ATM-027 in a baseline versus treatment magnetic resonance imaging-monitored study. Expansion of Vbeta5.2/5.3(+) T cells has been demonstrated in the peripheral blood, cerebrospinal fluid, and brain lesions of MS patients. In a phase I study, ATM-027 depleted these cells in peripheral blood and, in parallel, T-cell MBP reactivity and IFN-gamma expression were reduced. We studied 59 patients with relapsing-remitting MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…Second, an increase of the proportion of V␤5.2/5.3-positive cells in PBL and CSF cells in MS patients was detected by FACS analysis. Furthermore, selective in vitro depletion of these T cell subsets resulted in a drastic decrease in the number of MBP-reactive and IFN-␥-secreting T cells (31,32). In addition to these findings, we showed in this study that V␤5.2 spectratype expansion was equally found in DRB1*1501-positive and -negative patients (Table II).…”
Section: Discussionsupporting
confidence: 68%
“…Second, an increase of the proportion of V␤5.2/5.3-positive cells in PBL and CSF cells in MS patients was detected by FACS analysis. Furthermore, selective in vitro depletion of these T cell subsets resulted in a drastic decrease in the number of MBP-reactive and IFN-␥-secreting T cells (31,32). In addition to these findings, we showed in this study that V␤5.2 spectratype expansion was equally found in DRB1*1501-positive and -negative patients (Table II).…”
Section: Discussionsupporting
confidence: 68%
“…ATM-027 is a recombinant humanized IgG specifically targeting vh5.2/5.3 T cells [30]. The drug is well tolerated but the reduction of disease activity as measured by MRI Gd-enhancing lesions was not statistically significant.…”
Section: Agents Already Tested In Msmentioning
confidence: 97%
“…3 Even though 1 phase 2 clinical trial did show consistent suppression of Vβ5.2/5.3 T cells, there were only minimal effects on MRI lesion reduction and contrast enhancement suppression. 100 A summary of some of the mAbs used in MS is listed in Table 1. Anti-CD154 or -CD40L Thromboembolic events 3,102 development and application of mAbs for MS has demonstrated that this disease is a heterogeneous immunopathologic process that does not uniformly respond to the same treatments.…”
Section: Other Mabsmentioning
confidence: 99%